A Leste do Éden: reconstruções de identidade de imigrantes em torno da música - Guerra, Paula (2016)
Music is a unique form of communication and across borders. Defending the existenceof a (re)materialization of culture in terms of contextual and relational practice, thepractice music activation sites are favored domains from which it can developattitudes and modes of interaction. This paper presents a set of musicalrepresentations extracted and analyzed from east immigrant speeches. Data werecollected through semi-structured interviews about belongings and musicalimmigrant affiliations. The results suggest that the culture is much more than a set ofideas and values. In line with previous literature data, the relationship between cultureand social structure cannot be characterized as a simple homology, but as a process of(re)continuous construction, where the diverse and plural identities emerge. Thisunderstanding is a fundamental contribution to the understanding ofmulticulturalism sociology where music stands out as one of the underlying principlesof social life, which reflects new models of migration integration.